Abnormal default-mode network homogeneity in first-episode, drug-naive major depressive disorder. - Wenbin Guo; Feng Liu; Jian Zhang; Zhikun Zhang; Liuyu Yu; Jianrong Liu; Huafu Chen; Changqing Xiao (PLoS ONE, 2014)
BACKGROUND: Default mode network (DMN) is one of the most commonly recognized resting-state networks in major depressive disorder (MDD). However, the homogeneity of this network in MDD is poorly understood. As such, this study was conducted to determine whether or not an abnormal network homogeneity (NH) of DMN is observed in patients with first-episode and drug-naive MDD. METHODS: Twenty-four first-episode drug-naive patients with MDD and twenty-four healthy control subjects participated in the study. NH and independent component analysis (ICA) methods were used to analyze data. RESULTS: Depressed patients exhibited a significantly increased NH in the left dorsal medial prefrontal cortex (MPFC) and decreased NH in the right inferior temporal gyrus (ITG) compared with the healthy control subjects. Receiver operating characteristic curves (ROC) were analyzed and results revealed that the NH values of MPFC and ITG could be applied as candidate markers with relatively high sensitivity and specificity to distinguish patients from healthy control subjects. No correlation was observed between the NH values of the two regions and clinical variables. CONCLUSIONS: Our findings suggested that an abnormal DMN homogeneity could be observed in MDD, which highlight the importance of the DMN in the pathophysiology of MDD.